5-Year results from the prospective European multi-centre study on decellularized homografts for pulmonary valve replacement ESPOIR Trial and ESPOIR Registry data. (15th April 2022) - Bobylev, Dmitry; Horke, Alexander; Boethig, Dietmar; Hazekamp, Mark; Meyns, Bart; Rega, Filip; Dave, Hitendu; Schmiady, Martin; Ciubotaru, Anatol; Cheptanaru, Eduard; Vida, Vladimiro; Padalino, Massimo; et al.
Abstract: OBJECTIVES: Early results from the prospective ESPOIR Trial have indicated excellent results for pulmonary valve replacement using decellularized pulmonary homografts (DPH). METHODS: A 5-year analysis of ESPOIR Trial patients was performed to provide an insight into the midterm DPH performance. ESPOIR Trial and Registry patients were matched with cryopreserved homografts (CH) patients considering patient age, type of heart defect and previous procedures to present the overall experience with DPH. RESULTS: A total of 121 patients (59 female) were prospectively enrolled (8/2014–12/2016), median age 16.5 years (interquartile range 11.2–29.8), and median DPH diameter 24 mm. One death (73 year-old) occurred during a median follow-up of 5.9 years (5.4–6.4), in addition to 2 perioperative deaths resulting in an overall mortality rate of 2.5%. One case of endocarditis in 637 patient-years was noticed, resulting in an incidence of 0.15% per patient-year. At 5 years, the mean peak gradient was 19.9 mmHg (9.9), mean regurgitation 0.9 (0.6, grade 0–3) and freedom from explantation/any reintervention 97.5% (1.5). The combined DPH cohort, n  = 319, comprising both Trial and Registry data, showed significantly better freedom from explantation for DPH 95.5% (standard deviation 1.7) than CH 83.0% (2.8) ( P  < 0.001) and less structural valve degeneration at 10 years when matched to 319 CH patients [DPH 65.5% (standard deviation 4.4) and CH 47.3% (3.7), P  = 0.11]. CONCLUSIONS: The 5-year data of the prospective ESPOIR Trial show excellent performance for DPH and low rates of adverse events. ESPOIR Registry data up to 15 years, including a matched comparison with CH, demonstrated statistically significant better freedom from explantation. Abstract : Decellularized pulmonary homografts (DPH) for pulmonary valve replacement (PVR) have shown superior results to standard cryopreserved homografts (CH) in several single-centre analyses [1–3] as well as in a recent meta-analysis including the initial results of a prospective multicentre study on DPH, the ESPOIR Trial, funded by the European Commission [4].